Docking, Not Fusion, as the Rate-Limiting Step in a SNARE-Driven Vesicle Fusion Assay - Smith, Elizabeth A. (The Biophysical Society, 2011)
In vitro vesicle fusion assays that monitor lipid mixing between t-SNARE and v-SNARE vesicles in bulk solution exhibit remarkably slow fusion on the nonphysiological timescale of tens of minutes to several hours. Here, single-vesicle, fluorescence resonance energy transfer-based assays cleanly separate docking and fusion steps for individual vesicle pairs containing full-length SNAREs. Docking is extremely inefficient and is the rate-limiting step. Of importance, the docking and fusion kinetics are comparable in the two assays (one with v-SNARE vesicles tethered to a surface and the other with v-SNARE vesicles free in solution). Addition of the V(C) peptide synaptobrevin-2 (syb(57–92)) increases the docking efficiency by a factor of ∼30, but docking remains rate-limiting. In the presence of V(C) peptide, the fusion step occurs on a timescale of ∼10 s. In previous experiments involving bulk fusion assays in which the addition of synaptotagmin/Ca(2+), Munc-18, or complexin accelerated the observed lipid-mixing rate, the enhancement may have arisen from the docking step rather than the fusion step.